Romanian entertainment shows through non-literary sources in the Tripolitan region (Albayan Scientific Journal, 2024)
There are many scenes of bloody sports performances that used to take place in the circular theater, we find them depicted on the walls and floors of public and private buildings, those scenes embody the armed conflict between gladiators, the struggle of predators among themselves, or their hunting by man, and they also embody war in all its meanings, and the bloodshed involved, this research deals with the study of entertainment shows, bloody sports and their various types, through some non-literary sources represented in Mosaic and mural paintings in the Libyan Tripoli region, and also aims to shed light on its role in the Tripolitania society during the Roman era, through the methodology of archaeological research Which is based on the description and analysis of paintings and scenes.